Analisis Komparatif Zona Agregat Halus Terhadap Kuat Tekan, Kuat Tarik Belah, dan Kuat Lentur Beton - Ni Wayan Pani Nadia Sari; Ni Komang Ayu Agustini; Aryastana, Putu (Universitas Bengkulu, 2025)
The performance and durability of concrete depend significantly on the quality of its components, particularly fine aggregates such as sand. These aggregates are categorized into four distinct gradation zones according to their particle size distribution. This study aims to analyze how different fine aggregate gradation zones affect the mechanical properties of standard concrete designed for a target compressive strength of 25 MPa. The experimental approach involved assessing material characteristics, designing concrete mixtures following SNI 03-2834-2000 guidelines, and conducting compressive, split tensile, and flexural strength tests after 7 days of curing. Results indicated that zone 2 fine aggregates yielded the maximum compressive strength (29.03 MPa) and split tensile strength (1.49 MPa), whereas zone 3 aggregates produced the highest flexural strength (2.71 MPa). These findings highlight the importance of selecting the optimal fine aggregate gradation zone to enhance concrete performance.